ANALISIS PERAN ORANG TUA DALAM MENGEMBANGKAN KEDISIPLINAN BELAJAR SISWA KELAS IV DI SDN 2 MUMBUL SARI - Nais Kusma Dewi; Muhammad tahir; Husniati Husniati (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to find out how the role of parents in developing the learning discipline of fourth grade students at SDN 2 Mumbul Sari. The type of research used was descriptive qualitative research, the subjects in this study were 10 parents of fourth grade students at SDN 2 Mumbul Sari, the data collection technique used was interviews and documentation and the instruments used were interviews and documentation based on the results of the interviews conducted that the role of parents in developing student learning discipline can be seen from several aspects firstly parents as educators (educators), parts of parents as educators to improve student learning discipline include: giving assignments to children, making study schedules at home, discipline in educating children the second is the role of parents as a motivator, namely: giving advice to children, giving attention to children, giving motivation to children thirdly parents as supervisors (supervisors) namely: supervising children in learning, recognizing learning techniques in children the last parent as the facilitator, namely providing facilities to children.